2014
DOI: 10.1071/ah12009
|View full text |Cite
|
Sign up to set email alerts
|

Generic drug prices and policy in Australia: room for improvement? A comparative analysis with England

Abstract: Despite recent reforms, the Australian Government continues to pay higher prices than its English counterpart for many generic medications. The results suggest that particular policy areas may benefit from review in Australia, including the length of the price-setting process, the frequency of subsequent price adjustments, the extent of price competition between originators and generics, medical professionals' knowledge about generic medicines and incentives for generic prescribing. WHAT IS KNOWN ABOUT THE TOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Use of technology : The main part of this theme is using of e-prescribing system by physicians ( 5 , 16 , 19 , 24 , 32 , 38 , 43 , 47 ). In this system, medicines are categorized into three tiers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Use of technology : The main part of this theme is using of e-prescribing system by physicians ( 5 , 16 , 19 , 24 , 32 , 38 , 43 , 47 ). In this system, medicines are categorized into three tiers.…”
Section: Discussionmentioning
confidence: 99%
“…In 14 countries, it is advised to use GS, including Norway, Ireland, and Poland. As well, the GS is mandatory in 14 US states alternatively, it is forbidden in five countries, including Bulgaria, Austria, and Belgium ( 3 , 5 , 19 , 23 , 25 , 28 , 29 , 31 33 , 35 , 38 , 40 , 46 , 58 61 ). Many studies have shown the efficiency of generic substitution policy and the right of pharmacists to dispense generics, regardless of whether the prescriber wrote the brand name or generic ( 62 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic compound patent for sofosbuvir expires in a number of patent-granting countries in 2025 [ 44 ]. Upon patent expiry, generics can be freely produced and disseminated, creating competition and reducing costs for governments and consumers [ 45 , 46 ]. For example, generic competition for HIV antiretroviral therapy (ART) contributed to a 99% price reduction [ 47 ].…”
Section: Intellectual Property Lawmentioning
confidence: 99%